The Implementation of Pancasila Values in Higher Education: A Lecturer's Perspective - Siregar, Elfrida Herawati; Utomo, Cahyo Budi; Pramono, Suwito Eko; Sholeh, Muh (Universitas Negeri Semarang, 2024)
This research aims to explore lecturers' views on the implementation of Pancasila values in higher education, as well as the challenges and strategies they use in the teaching process. Through in-depth interviews, classroom observations, and document analysis, this study finds that lecturers face various challenges, including students' lack of interest, material relevance, teaching methods, and resource limitations. Lecturers employ interactive learning methods, technology, extracurricular activities, experience-based projects, and reflection-based evaluations to help students internalize Pancasila values. These findings align with previous research highlighting the crucial role of lecturers and innovative strategies in Pancasila education. The study concludes that stronger institutional support is needed to address these challenges and strengthen the role of lecturers in shaping students' character based on Pancasila values. With adequate support, lecturers can be more effective in creating relevant and dynamic learning experiences, which will help students apply Pancasila values in their daily lives.